2003
DOI: 10.1055/s-2003-44289
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Cerebral Metabolism in Patients with Diabetes Mellitus Studied by Proton Magnetic Resonance Spectroscopy

Abstract: To evaluate possible pathophysiologic links between cerebral changes in diabetic patients detected by proton magnetic resonance spectroscopy and clinical as well as laboratory parameters. The brains of 30 patients with diabetes mellitus and 30 healthy volunteers were examined using a STEAM sequence (TR 1500 ms, TE 20 ms). We measured in occipital gray matter and parietal white matter in a 1.5-Tesla magnet. Laboratory parameters were acquired before and after the examination. In diabetic patients a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 21 publications
9
40
3
2
Order By: Relevance
“…Most recently, myo-inositol increases in white matter were seen in diabetic patients with retinopathy and autonomic neuropathy (Makimattila et al, 2004). It has been suggested that the increases seen in myoinositol found in diabetic patients are associated with gliosis (Geissler et al, 2003). This hypothesis is consistent with our findings showing significant myo-inositol changes only in frontal white matter.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Most recently, myo-inositol increases in white matter were seen in diabetic patients with retinopathy and autonomic neuropathy (Makimattila et al, 2004). It has been suggested that the increases seen in myoinositol found in diabetic patients are associated with gliosis (Geissler et al, 2003). This hypothesis is consistent with our findings showing significant myo-inositol changes only in frontal white matter.…”
Section: Discussionsupporting
confidence: 92%
“…For Brain MRS in type 2 diabetes and major depression O Ajilore et al example, increases in myo-inositol, glucose, and choline were seen in both gray and white matter in an early study of diabetic patients (Kreis and Ross, 1992). Also, myoinositol : creatine ratios have been shown to be increased in diabetic patients in both gray and white matter (Geissler et al, 2003). Myo-inositol increases have also been demonstrated in animal models of diabetes, albeit in hippocampus (van der Graaf et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, under chronic hyperglycemia, the accumulation of organic osmolytes in the hippocampus is suitable to avoid ioninduced perturbation of protein function. Consistent with this, a high concentration of myo-inositol has also been reported in the hippocampus of Zucker diabetic fatty rats compared to controls (van der Graaf et al, 2004) and in the brain of diabetes patients (Geissler et al, 2003;Kreis and Ross, 1992). Thus, the study of the neurochemical profile supports the hypothesis that hyperglycemia-induced hippocampal dysfunction mainly involves deregulation of osmotic balance rather than modification of primary metabolism.…”
Section: Diabetic Encephalopathysupporting
confidence: 77%
“…Metabolic disorders such as diabetes result in alterations of the neurochemical profile (Duarte et al, 2009a;Geissler et al, 2003;Kreis and Ross, 1992;van der Graaf et al, 2004), regarding metabolites involved in energy metabolism. Hyperglycemia increases brain levels of glucose and β-hydroxybutyrate, is an indicator of ketoacidosis, and is quantifiable at a high magnetic field (Duarte et al, 2009a;Lei et al, 2010a).…”
Section: Energy Metabolismmentioning
confidence: 99%